Pembelajaran Berkualitas bagi Anak-Anak Desa dan Peran UMKM dalam Menggerakkan Perekonomian Lokal Warga Dusun Krinjing Desa Purwosari Salaman Kabupaten Magelang - Ahmad Shiddiq Pribadi; Elvira Ayu Lestari; Nadya Febby Aulia; Yeni Karlina Enmopiana; Mohammad ‘Ulyan (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Krinjing Hamlet is a hamlet located in Purwosari Village, Salaman District, Magelang Regency, Central Java, which consists of 1 RW and 2 RT. There are several activities carried out by the Purwosari Village KKN Group. These activities consist of the education sector and the industrial sector. The first activity carried out by the Purwosari Village KKN group was effective learning. The second activity is providing outreach to strengthen and develop digital marketing for MSME players. The Purwosari Village KKN group held a socialization on strengthening and developing digital marketing for MSME players, including the creation of NIBs. This socialization activity was attended by 60 residents of Krinjing Hamlet. The aim of holding this outreach is to develop the potential of MSMEs in Krinjing Hamlet. The implementation of effective learning activities from the Purwosari Village KKN Group aims to build the character of the future generation which can instill a sense of social responsibility. As the hope and future of the nation, the younger generation must understand the importance of social responsibility towards the environment and surrounding community. Apart from that, activities related to MSME actors, namely outreach on strengthening and developing MSMEs, aim to encourage MSME actors to be more innovative in running their businesses.